Absorption-dominated electromagnetic interference shielding assembled composites based on modular design with infrared camouflage and response switching. (5th January 2023) - He, Jie; Han, Mengjie; Wen, Kai; Liu, Chunlei; Zhang, Wei; Liu, Yaqing; Su, Xiaogang; Zhang, Cunrui; Liang, Chaobo
Abstract: Absorption-dominated electromagnetic interference (EMI) shielding materials are ideal for preventing electromagnetic pollution, but they suffer from complex structural design, poor performance stability, and narrow operating bands. Here, silica/carbon nanotubes/polyimide-silver nanowires/cellulose nanofibers (SiO2 /CNTs/PI-AgNWs/CNF) composites are prepared based on the principle of split conductive modular design. According to the use requirements, the electromagnetic module is reasonably assembled, thus achieving a high degree of unity in electromagnetic wave absorption and shielding. In detail, the SiO2 /CNTs/PI foam with progressive long channel structure has good impedance matching and provides excellent electromagnetic wave absorption. The highly conductive AgNWs/CNF film ensures excellent EMI shielding performance. The reflection shielding effectiveness (SER ) is as low as 0.023 dB at an average EMI SE of 110 dB for the assembled composite, corresponding to an ultra-low reflectivity (R) of 0.00538. In addition, the assembled composite also has an autonomous switching function between infrared camouflage and infrared response, due to the low infrared emissivity characteristic and Joule heating effect of AgNWs/CNF film, as well as the thermal insulation properties of SiO2 /CNTs/PI foam. This flexible work will stimulate adaptive applications of EMI shielding materials in radar stealth and infrared camouflage environments. Graphical abstract: Image 1 Highlights: Absorption-dominated electromagnetic interference (EMI) shielding materials. Flexible split conductive modular design principles. Autonomous switching function between infrared camouflage and infrared response.